A Liberal Analysis of Religious Exemptions to Public Accommodation Laws - (:unkn) unknown (My University, 2018)
In 2015, the United States Supreme Court effectively made same-sex marriage legal throughout the country. Writing for the majority, Justice Kennedy opined that not extending marriage equality to same-sex couples violated both their autonomy and their right to equal dignity under the law. Three years earlier, a same-sex couple visited Masterpiece Cakeshop, a bakery in Colorado, and requested that the owner design and create a cake to celebrate their same-sex wedding. The owner declined, advising the couple that he did not provide wedding cakes for same-sex weddings due to his religious beliefs. He was found guilty of violating the Colorado Anti-Discrimination Act for discrimination on the basis of sexual orientation. In this paper, I present a liberal argument for the proposition that narrowly-tailored exemptions ought to be provided to wedding vendors such as Phillips with religious objections to same-sex marriage. In arguing for this claim, I provide a compromise between those who believe that the relevant anti-discrimination provisions should be categorically applied to all businesses open to the public and proponents of religious liberty who maintain that any business with religious objections to same-sex marriage should be able to refuse service to same-sex couples.
Keywords: Free Speech; Liberalism; Masterpiece Cakeshop; Religious Liberty; Religous Exemptions; Same-Sex Marriage